Strategi Guru dalam Menghadapi Siswa Lamban Belajar (Slow Learner) Pada Proses Pembelajaran Tematik - Humaidah Fatimah Parapat (Journal of Islamic Education, 2020)
Strategy is one of the series of activity, which is made and implemented to reach particular goal. Slow learners are students who are slower in underastanding a concept than other fellow students of the same age. The strategies used by teacher in the learning process is a very crucial part to help slow learners who have a low ability.The results of the study indicate that: (1) the teachers of SDN Ketawanggede Malang create a planning before starting the thematic learning process by preparing RPP (lesson plan). They add a modification such as material and learning objective for the slow learners. (2) Both school conduct introductory activities in the thematic learning implementation process, which are given by the teachers, by giving apperception delivering the learning objectives, and giving motivation to all student including slow learners. The slow learners do the same activities as what other students do. In the closing activities, the teachers usually perfom a question-answer session to conclude the lesson given and give assignments for the slow learners based on their abilities. (3) The evaluation and assesment of the  of the thematic learning process for slow learners are not different with what are given to the non-slow learners .(4) There are some different strategies given by the teachers in treating slow learners in both schools, namely: the modified lesson plan including the material and learning objectives as performed by SDN Ketawanggede Malang, special ways implemented by the homeroom teachers to improve the slow learners’ ability in class, and the treatment given by special shadow teachers that really helps the slow learners to improve. The similarities found in both schools are the facts that the teachers in both schools are the facts that the teachers in both schools do not have special strategy, method, and learning media to help slow learners to be able to understand the materials conveyed by the teachers easily.